“I eat more salads because they are good for health”: Cooking, Eating and Informal Learning among Recent Chinese Immigrants - Willa Liu, Lichun (Cuizine)

(untitled) (McGill University Library, 2009)
AbstractDrawing on data from a Canadian survey on work and lifelong learning as well as in-depth interviews with recent Chinese immigrants in the Toronto area, this paper examines how cross-cultural migration influences food-related housework and health, and the informal learning involved in such activities. By focusing on gender, this paper reveals how immigration has (or has not) changed the gendered division of food work amongst participants in the study and influenced food habits (for example, in cooking and diet), as well as ways in which participants have (or have not) learned to accommodate these changes and to maintain their health through food and cooking.